RELIGIOUS DISCOURSE ON THE NEWS OF COVID-19 IN INDONESIAN ONLINE MASS MEDIA - Ihsan Sa'dudin; Eka Safitri; Sutrimo Sutrimo (UIN Siber Syekh Nurjati Cirebon, 2022)
This study examines religious discourse on the news of Covid-19 in sindonews.com, Republika.co.id, and tempo.co. The Fairclough Model Critical Discourse Analysis approach is used in this study to examine the macrostructure, superstructure, and microstructure of religious discourse in three Indonesian online mass media. Macrostructure analysis is used to describe in general the religious narrative on each news topic and the important points that refer to major themes. Superstructure analysis aims to interpret the themes that exist in the media and news schemes that are displayed in the news text. While the microstructure is used to represent the linguistic aspects of the news narrative, namely the semantic aspect, the syntactic aspect, and the stylistic aspect. The results of the study show that religious discourse related to covid-19 news on Republika online prioritizes the use of overviews sourced from the Quran and the hadith. The dialogue on religious teachings with the factual issue of Covid is used to build religious discourse in the news of covid-19 on Sindonews Online. Meanwhile, Tempo online uses persuasive language about the role of religion during the COVID-19 pandemic. While the microstructure is used to represent the linguistic aspects of the news narrative, namely the semantic aspect, the syntactic aspect, and the stylistic aspect.